The Assessment of the Relationship Between Employee Empowerment and Span of Control - Alam, Amna; Gill, Mahnoor; Racheal, Saba; Anwar, Ghazala; Anwar, Humaira (Biological and Clinical Sciences Research Journal, 2026)
Employee empowerment is increasingly recognized as an essential element of effective organizational management, particularly in healthcare institutions where frontline staff play a critical role in service delivery. Organizational structures, including managerial span of control, may influence employees' levels of empowerment. Understanding this relationship is important for improving leadership practices and enhancing workplace efficiency in nursing settings. Objective: To assess the relationship between span of control and employee empowerment among nurses working at Ittefaq Hospital Trust, Lahore. Methods: A descriptive correlational study was conducted among 153 charge nurses at Ittefaq Hospital Trust from January 2025 to June 2025. Participants were selected using purposive sampling. Data were collected using a structured questionnaire adopted from the literature that assessed demographic characteristics, perceptions of employee empowerment, organizational authority, communication practices, autonomy, and leadership behaviors related to span of control. Ethical approval and written informed consent were obtained before data collection. Data were analyzed using SPSS, and descriptive statistics, including frequencies and percentages, were calculated. Correlational analysis was performed to examine the relationship between employee empowerment and span of control, with a significance level set at p < 0.05. Results: Most respondents were aged 25–30 years (82.4%), worked in general departments (74.5%), held General Nursing qualifications (79.7%), and had 1–5 years of professional experience (78.4%). A large proportion of nurses reported limited organizational empowerment, with 64.7% strongly disagreeing that the organizational structure provides employees with full authority. Similarly, 39.9% disagreed that they felt personally empowered in their work processes. Leadership behaviors associated with span of control were reported to occur only sometimes by many participants, including role modeling (50.3%) and managers' conflict resolution (47.1%). These findings suggest limited structural empowerment and inconsistent leadership practices within the organizational environment. Conclusion: The study indicates that nurses experience relatively low levels of organizational empowerment, which may be associated with managerial span of control and leadership practices. Strengthening supportive leadership behaviors, improving communication, and optimizing supervisory structures may enhance employee empowerment and organizational effectiveness in nursing settings.